Surgery with Cross-Speciality Approach to Pediatric Gastric Trichobezoar Obstruction In Indonesia: A Case Report - Hariono, Hariono; Fardiansyah, Mochamad Syahroni; Ekaputra, Anthony (Journal of Agromedicine and Medical Sciences, 2025)
Trichobezoar, a rare conditions in pediatric patients affecting less than 1%, often associated with trichotillomania, can lead to obstructive symptoms in severe cases. However, none of the published cases have documented surgical intervention alongside interdisciplinary collaboration in Indonesia that comply SCARE 2023. This case report aims to enhance pediatric trichobezoar literature, by sharing tailored approaches for limited-resource settings and the role of multidisciplinary strategies with surgical intervention. We represent a case of an 8-year-old girl from a low resource setting with a recent episode of vomiting after consuming her own hair for the past six months. Esophagogastroduodenoscopy revealed hair bezoar completely occluding the gastric pylorus. The patient underwent laparotomy with gastrotomy to extract the bezoar. She was then treated by the psychiatrist for trichotillomania, by the pediatrics for catch-up growth, and by the dermato-venereologist for alopecia. No complications or adverse events were observed. Keywords: trichobezoar, gastric obstruction, pediatrics, Indonesia, pediatric surgery